2003
DOI: 10.1111/j.1464-410x.2004.04571.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of palpable and impalpable cryptorchid testes using CD‐99 immunohistochemistry

Abstract: tubule (MGCT) were calculated using immunohistochemistry for CD-99, a Sertolicell marker, to classify germ cells more accurately. RESULTSSixty-three testes (33%) were impalpable; the median age at the time of surgical exploration was 23 months for both groups. The mean ( SD ) testicular volume for the impalpable and palpable groups were 0.83 (0.38) and 1.22 (0.54) mL, respectively. Using fitted curves of size vs age, impalpable testes were smaller than palpable testes at all ages, with the difference nearly st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…There were significant variations in the tubular diameter and number of germ cells, with larger tubules and more germ cells in those patients aged <1 year. These findings are consistent with other reports and suggest that our population is representative [8,9]. There was no correlation between testicular position and histological findings, probably because there were relatively few patients and, in this small series, we were unable to take into account the variations in the ages of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…There were significant variations in the tubular diameter and number of germ cells, with larger tubules and more germ cells in those patients aged <1 year. These findings are consistent with other reports and suggest that our population is representative [8,9]. There was no correlation between testicular position and histological findings, probably because there were relatively few patients and, in this small series, we were unable to take into account the variations in the ages of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Subanalysis of abdominal and extra-abdominal testes by Abrahams et al confirmed no significant differences in size [11]. Lee et al also showed that preoperative testicular location of the undescended testis in men with previous unilateral cryptorchidism was not a major determinant of fertility, according to paternity, sperm count, or hormone levels [12].…”
Section: Discussionmentioning
confidence: 86%
“…This result explains the damage to future spermatogenesis in unilateral cryptorchidism and supports the validity of early orchiopexy for the cryptorchid child. Some studies have revealed a correlation between testicular volume and the age of cryptorchid children at orchiopexy [11,13,14]. Beltran-Brown and Villegas-Alvarez found that testes further from the scrotum were smaller than those found lower down [13].…”
Section: Discussionmentioning
confidence: 96%
“…The present results can be best explained by considering the processes that might cause histological lesions of the cryptorchid testes [26]. Although there is some controversy, several studies have shown that newborns with typical cryptorchidism and inguinal hernias have a normal number of germ cells, but that this number declines with age [27,28]. It is thought that cryptorchid patients have hypogonadism (lower than normal secretion of gonadotrophins and testosterone) that occurs during the normal testosterone surge of the first 4–6 months of life.…”
Section: Discussionmentioning
confidence: 95%